Variable Occipital Sulci: A Useful Guide to Identify the Focal Lesions on the Occipital Lobe - Lokadolalu Chandracharya Prasanna; Lydia S. Andrade (Online Journal of Health & Allied Sciences, 2019)
Objectives: The position and extent of human occipital cortical areas defined either architectonically or functionally have characteristic relationships to the occipital sulci, their banks and fundi or to points of sulcal intersections. The aim of our study was to define the variability of the human occipital sulci with particular regard to the sulcal: (1) presence, (2) position, (3) extent, (4) intersections and (5) length. Materials and method: Investigation was performed on 40 human formalin-fixed cerebral hemispheres used for undergraduate teaching in Kasturba Medical College, Manipal Academy of Higher Education, Manipal, Karnataka, India. Main occipital sulci were observed extensively along the superolateral surface of the occipital lobe. Results: Six types of occipital sulci on the superolateral surface were compared with the previous authors. Conclusion: Well established and constant occipital sulci, or the points of their intersections, may be used as useful anatomical landmarks during less invasive neurosurgical procedures.